The relationship between the selection of the triage category with the delay system of stemi patients in the adam malik hospital Medan. - Yusuf Hanafiah; Asti Melani Astari; Dina Dewi Sartika Lestari Ismail (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Background: The process that occurs in the emergency room is a crucial process for treating STEMI. At this time is when the diagnosis is made in patients and it is decided to take further action. Delay or delay will be very detrimental to the patient if it occurs, especially when the STEMI patient is in the ER. One of the things that might cause system delays in the ED is the selection of triage categories for STEMI patients. The triage chosen for the patient will determine the patient's waiting time and the patient urgency to be treated, allowing the patient to wait longer if placed in category 2 or category 3. Methods: This quantitative study uses an analytic observational design with a cross-sectional type. In this study, observations were made of the effect of selecting the triage category with the delay system for STEMI patients in the emergency room. The population in this study are all STEMI patients who will be undergoing PCI during the study period, from September to November 2022. The sampling technique used is total sampling because the population is less than 30. Data analysis will use Spearman because the data is on a nominal and ordinal scale. Result: the significant result is 0.01 or less than 0.05, so the two factors correlate. Then the correlation coefficient value is 0.342. This value indicates a weak correlation value because it is between 0.26 and 0.5. The direction of the correlation is positive, which means the correlation is unidirectional Conclusion: there is a correlation between the selection of triage categories carried out by emergency room nurses and the delay system that occurs in the emergency department of the Haji Adam Malik General Hospital Medan. Abstrak: Latar belakang : Proses yang terjadi di IGD merupakan proses yang krusial bagi penanganan STEMI. Pada waktu ini merupakan saat ditegakkan nya diagnosa pada pasien dan diputuskan untuk dilakukan tindakan selanjutnya. Keterlambatan atau delay akan sangat merugikan pasien jika terjadi terutama jika terjadi saat pasien STEMI berada diIGD. Salah satu hal yang kemungkinan menyebabkan system dellay di IGD adalah pemilihan kategori triase untuk pasien STEMI. Triase yang dipilih untuk pasien akan menentukan waktu tunggu pasien dan urgensi pasien tersebut untuk ditangani yang memungkinkan pasien akan lebih lama menunggu jika diletakkan padakategori 2 atau kategori 3.  Metode : Penelitian ini merupakan penelitian kuantitatif dengan menggunakan rancangan observasional analitik dengan jenis cros sectional. Dalam penelitian ini dilakukan pengamatan  terhadap pengaruh pemilihan kategori triase dengan system delay Pasien STEMI di ruangan IGD. Populasi pada penelitian ini merupakan seluruh pasien STEMI yang akan dilakukan tindakan PCI selama rentang waktu penelitian yaitu dari bulan september hingga november 2022. Teknik sampling yang digunakan merupakan total sampling karena populasi kurang dari 30 Analisa data akan menggunakan spearman karena data berskala nominal dan ordinal.  Hasil : hasil signifikansi adalah sebesar 0,01 atau kurang dari dari 0,05 maka kedua faktor tersebut memiliki korelasi. Kemudian untuk nilai corelation coeffition adalah sebesar 0,342. Nilai tersebut menunjukkan nilai korelasi lemah karena berada antara 0,26 hingga 0,5. Arah korelasinya adalah positif yang berarti korelasi searah Kesimpulan : terdapat korelasi antara pemilihan kategori triase yang dilakukan oleh perawat IGD dengan system delay yang terjadi di IGD RS umum pusat Haji Adam Malik Medan